1996
DOI: 10.1128/iai.64.12.4976-4983.1996
|View full text |Cite
|
Sign up to set email alerts
|

Initial route of antigen administration alters the T-cell cytokine profile produced in response to the mouse pneumonitis biovar of Chlamydia trachomatis following genital infection

Abstract: A Th1-type response develops following vaginal infection with the mouse pneumonitis biovar of Chlamydia trachomatis (MoPn). Since the type of response, i.e., Th1 versus Th2, can be influenced by factors present during T-cell activation, we examined the effects of different routes of MoPn administration on the cytokine profile and resistance against infection following a MoPn vaginal challenge. A dominant Th1-type cytokine profile developed in mice given live MoPn via the intranasal, oral, and vaginal routes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…Subcutaneous administration of bacteria induced a more mixed type of response. In a recent study [36] it was also reported that the s.c. injection of the intracellular pathogen Chlamydia trachomatis generated a less polarized response than mucosal immunization that induced a Th1 profile. Since both organisms are intracellular pathogens, the cell types that are infected after s.c. administration may condition the establishment of a more balanced response.…”
Section: Discussionmentioning
confidence: 85%
“…Subcutaneous administration of bacteria induced a more mixed type of response. In a recent study [36] it was also reported that the s.c. injection of the intracellular pathogen Chlamydia trachomatis generated a less polarized response than mucosal immunization that induced a Th1 profile. Since both organisms are intracellular pathogens, the cell types that are infected after s.c. administration may condition the establishment of a more balanced response.…”
Section: Discussionmentioning
confidence: 85%
“…47 No obvious difference was observed in the numbers of DC subsets between PGE 2 and control mice in the spleen early after infection (data not shown) consistent with reports that the ILN is the primary site of T-cell activation early after infection in a genital infection. 48,49 These results imply that PGE 2 affects the migration of cDCs, but not pDCs, in vivo.…”
Section: Exogenous Pge 2 Elevates Genital Tract Tissue Levels Of Pge mentioning
confidence: 76%
“…That the host does indeed respond to GI tract infection was noted by the presence of a strong local and systemic antibody response as well as a positive proliferation response in the MLN and ILN. Moreover, previous studies with oral immunization with viable organisms in both mouse and guinea pig models have demonstrated a substantial humoral and cell-mediated protective response to genital tract challenge (Nichols et al, 1978;Rank et al, 1990;Kelly et al, 1996). The absence of an inflammatory response in conjunction with clear evidence for active replication of chlamydiae as evidenced by successful isolation could be the result of numerous well-documented down-regulatory mechanisms elicited by other gut microbiota (Round & Mazmanian, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Regardless of the mechanisms by which chlamydiae survive in the local GI tract milieu, oral infection clearly activates an adaptive immune response that may manifest protection in other mucosal sites. In both mouse and guinea pig models, oral infection can elicit a protective response in the genital tract resulting in a shorter course of infection with lower peak infection levels (Nichols et al, 1978;Rank et al, 1990;Kelly et al, 1996). We noted many years ago that serum antibodies to all chlamydial antigens actually increased over time and that antibody to higher-molecular-weight proteins appeared consistently 90-100 days after infection (Ramsey et al, 1989).…”
Section: Discussionmentioning
confidence: 99%